دور الرضا الوظيفي في تحسين الخدمة العمومية: دراسة حالة مؤسسة سونلغاز -الأغواط - رحماني عبد الكريم; شكالي محمد; نبق قويدر (جامعة عمار ثليجي -الأغواط, 2022)
Job satisfaction has always been considered one of the topics of interest for many writers, thinkers, and researchers in the field of management sciences and therefore they must seek job satisfaction and its role in their personal and professional lives, Job satisfaction significantly affects staff behavior and performance And it constitutes an essential impetus to outstanding achievement and this has the benefit for enterprises and workers. This was demonstrated in our applied study by measuring the impact of job satisfaction on performance at Sonelgaz; this is based on the questionnaire and the interview with a sample consisting of executive agents, qualified agents, framers, and sublime frames. Then the data obtained were analyzed and results were reached that determined the extent of the impact of job satisfaction on performance in the institution under study. Keywords: job satisfaction, job performance.